Parallel proximal point methods for systems of vector optimization problems on Hadamard manifolds without convexity. (1st February 2020) - Ceng, L. C.; Li, X.; Qin, X.
ABSTRACT: In this paper, the local weak Pareto optimality conditions for nonsmooth vector optimization problems are presented on Hadamard manifolds. Some convergence results of the parallel proximal point algorithms for finding a solution of vector optimization problems are established.